Reflections on the Neches : a Naturalist's Odyssey along the Big Thicket's Snow River. - Watson, Geraldine Ellis (Temple Big Thicket Series #3., 2003)
A sixty-three-year-old woman builds a backwater boat and journeys down the Neches River in East Texas, telling both the story of her river float trip and the natural history and folklore of the region. Profusely illustrated with maps, drawings, and photographs, it will appeal to all interested in the Big Thicket region and those indulging a feeling of wanderlust-and float trips-down the river. "Should become an environmental classic."--Thad Sitton.